EDUCATIONAL FINANCE IN WESTERN EUROPE: SOME EXPERIENCES FROM A TANGLED WEB - Werner, Jan (Journal of European Economy, 2017)
Education is one of the most important services provided by public governments in almost every country worldwide. However, the most important cross-country observations about education – like the PISA report by the OECD or the TIMSS by the IEA – focus only on international benchmarks to compare the knowledge capacity of pupils. This paper provides a general overview of the different forms how education expenditures are financed in ten European countries. We observe the educational system in Austria, Belgium, Denmark, France, Germany, Italy, Spain, Sweden, Switzerland and the United Kingdom and point out the similarities and national distinctions.